Peristaltic flow of magnetized hyperbolic tangent fluid through an asymmetric channel in the presence of homogeneous-heterogeneous reactions - Mariam Sheikh; Muhammad Rizwan; Jafar Hasnain; Zaheer Abbas; Muhammad Yousuf Rafiq (Advances in Mechanical Engineering)
The hyperbolic tangent fluid model accurately captures the shear-thinning phenomenon and is widely used in both laboratory experiments and industrial applications. The primary aim of this research is to investigate the key characteristics of the peristaltic flow of electrically conducting hyperbolic tangent fluid through an asymmetric channel, considering the effects of homogeneous and heterogeneous reactions. Slip conditions at the sinusoidal channel walls are also incorporated. The resulting nonlinear equations are solved using the lubrication theory approximation, which is particularly relevant for predicting physiological characteristics, such as blood flow dynamics. Analytical solutions for velocity, pressure gradient, streamlines, and concentration distributions are obtained using the regular perturbation technique. The influence of various parameters on these distributions is presented through graphical analysis. Additionally, the pressure rise per wavelength along the channel walls is computed numerically. The results indicate that homogeneous and heterogeneous reaction parameters exhibit opposing effects on the concentration field. Furthermore, increasing the magnetic parameter leads to a reduction in fluid velocity. This study has practical applications, including the use of peristaltic pumps in the chemical and pharmaceutical industries, particularly for drug delivery systems.